Understanding and Mitigating Ageing in Nuclear Power Plants - Materials and Operational Aspects of Plant Life Management (PLiM) - Tipping, Philip G. (Woodhead publishing series in energy, 2010)
This book reviews the ageing-degradation mechanisms of materials used in nuclear power plant structures, systems and components, their relevant analysis and mitigation paths, and reactor-type specific plant life management (PLiM) practices. Obsolescence and other less obvious ageing-related aspects in nuclear power plant operation are also examined in depth. Part One introduces the role of nuclear power in the global energy mix, and the importance and relevance of PLiM for the safety regulation and economics of nuclear power plants. Key ageing degradation mechanisms and their effects in nuclear power plant systems, structures and components are reviewed in Part Two, along with routes taken to analyze the ageing of materials and to mitigate or eliminate ageing degradation effects. Part Three reviews analysis, monitoring and modelling techniques applicable to the study of nuclear power plant materials. Part Four reviews the particular ageing degradation issues, plant designs, and application of PLiM practices in a range of commercial nuclear reactor types. This book is a standard reference for all nuclear plant designers, operators, and nuclear safety and materials professionals and researchers.